2009
DOI: 10.1111/j.1601-5223.1978.tb01607.x
|View full text |Cite
|
Sign up to set email alerts
|

Low enzyme gene variability in Hymenoptera as a consequence of haplodiploidy

Abstract: Enzyme gene variability in fifteen hymenopteran species, mainly bees, has been studied. The species were Apis mellifera L., six Bombus species, Macropis labiata F., Colletes succincta L., three Andrena species, Vespula vulgaris L., Mimesa equestris F. and Pontania vesicator Bremi. The hymenopteran species reproduce by arrhenotokous parthenogenesis so that the males are haploid and the females are diploid. The present results, as also the earlier studies, show that the number of polymorphic loci and the amount … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
1
8

Year Published

2010
2010
2010
2010

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 82 publications
(20 citation statements)
references
References 16 publications
0
11
1
8
Order By: Relevance
“…Eusocial Hymenoptera such as bumblebees (e.g., Takahashi et al 2008) may be more suitable subjects for such a test than the largely solitary and subsocial orchid bees (cf. Cocom Pech et al 2008) because hymenopteran eusociality is associated with reduced genetic diversity and low N e (Pamilo et al 1978, 1997; Graur 1985; Hedrick and Parker 1997; Chapman and Bourke 2001; Packer and Owen 2001).…”
Section: Discussionmentioning
confidence: 99%
“…Eusocial Hymenoptera such as bumblebees (e.g., Takahashi et al 2008) may be more suitable subjects for such a test than the largely solitary and subsocial orchid bees (cf. Cocom Pech et al 2008) because hymenopteran eusociality is associated with reduced genetic diversity and low N e (Pamilo et al 1978, 1997; Graur 1985; Hedrick and Parker 1997; Chapman and Bourke 2001; Packer and Owen 2001).…”
Section: Discussionmentioning
confidence: 99%
“…Tables 1-3 indicate the main collection sites for each species. The material which has not been presented in our earlier reports is given in Table 1, whereas Tables 2 and 3 summarize both the new and old results (see PAMILO et al 1978;PEKKARINEN 1979). We have also increased the sample size in some populations included in our previous reports; these data are incorporated in the figures of Tables 2 and 3.…”
Section: Methodsmentioning
confidence: 99%
“…The earlier studies on enzyme gene variation in bumblebees have revealed a low level of heterozygosity in the species studied (SNYDER 1974;PAMILO et al 1978;PEKKARINEN 1979). Low levels, or absence, of enzyme gene variation has also been reported in other bees (SNYDER 1974;SYLVESTER 1976;PAMILO et a]. 1978;WAGNER and BRISCOE 1983) as well as in other hymenopterans (see PAMILO and CROZIER 1981 for a review;MENKEN 1982;BERKELHAMER 1983).…”
mentioning
confidence: 89%
“…Em teoria, os organismos haplodiploides deveriam possuir uma menor variabilidade genética do que os organismos diploides, devido à rápida eliminação dos alelos deletérios e fixação dos alelos vantajosos via machos (Suomalainen 1962) e ao seu menor número populacional efetivo (Crozier 1976). Estudos com locos enzimáticos e microssatélites de fato mostraram menor variabilidade genética em insetos haplodiploides (Metcalf et al 1975;Pamilo et al 1978;Lester & Selander 1979;Berkelhamer 1983;Hedrick & Parker 1997;Packer & Owen 2001).…”
Section: Abelhas Como Modelo Para Estudos De Genética De Populações Iunclassified
“…Dessa maneira, por apresentarem menos indivíduos reprodutivos por área, essas espécies possuem menor tamanho populacional efetivo do que espécies de abelhas solitárias (Pamilo et al 1978). Contudo, não foram encontradas diferenças significativas na variabilidade genética entre espécies eussociais e solitárias (Pamilo et al 1978;Berkelhamer 1983;Hedrick & Parker 1997;Packer & Owen 2001 Cameron et al 2011;Whitehorn et al 2011). Portanto, esse é mais um processo pelo qual populações com baixa diversidade genética podem diminuir seu tamanho populacional e até se extinguir.…”
Section: Abelhas Como Modelo Para Estudos De Genética De Populações Iunclassified